When Moral Beliefs Translate into Behavior: Ethical Leadership, Moral Efficacy and Procedural Justice in Predicting Workplace Deviance (Journal of Asian Development Studies, 2026)
The proposed research examines the effects of perceived ethical leadership on employee deviant behavior mediated by moral efficacy and moderated by procedural justice using the theoretical constructs of Social Cognitive Theory. Based on Social Cognitive Theory, a mediated moderation model will be tested where perceived ethical leadership will be found to have a positive effect on moral efficacy, which is predicted to have a negative effect on workplace deviance; and where perceived procedural justice will moderate the latter effect. The cross-sectional survey approach was chosen for the study, where 164 full-time employees participated and provided answers to self-administered questionnaires, which was followed by Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The results of the study show that there is a direct, positive effect of perceived ethical leadership on moral efficacy and a negative correlation between moral efficacy and deviant behavior at work. Partial least squares path analysis reveals that the indirect effect of ethical leadership on deviant behavior occurs through moral efficacy. At the same time, perceived procedural justice was found to moderate the latter negative relationship, indicating that high levels of procedural justice lead to a higher correlation. In other words, deviant behavior occurs less often when employees believe that organizational procedures are fair. The contribution of the study includes shifting the emphasis from deficit to capability approaches to explaining deviant behavior through moral efficacy. The findings also confirm the influence of the contextual aspect on the behavior, namely procedural justice.